How Do Publicly Listed Companies Report on Sustainability? A Mapping of the Standard/Framework Used By Industrial Firms in the Philippines - LEGASPI, Joy Lynn R.; AVILA, Elyjah Thomas T.; CASTRO, Maha Bianca Charisma C. (International Journal of Environmental, Sustainability, and Social Science, 2024)
The study aims to determine what kind of submission industrial firms do and the standard/framework industrial companies use to comply with the Securities and Exchange Commission (SEC) issued Memorandum Circular (MC) No. 4, series of 2019. A reporting template that serves as a guide to Publicly-Listed Companies to disclose economic, environmental, and social effects in compliance with globally accepted standards. The study considered the seventy-two (72) subsectors of publicly listed industrial companies. The annual report and sustainability report in 2020 were gathered from the Philippine Stock Exchange and company websites. The analysis was conducted by listing the companies and finding out if the company disclosed or did not disclose their sustainability report and presented through trends, frequencies, characteristics, and categories. The study revealed that the most common format and framework used was the SEC Sustainability Reporting Template. As for the disclosures, the majority of the companies disclosed their scope and boundaries, materiality assessment, and UN Sustainable Development Goals, while the majority of the companies did not disclose their external assurance and sustainability governance and management system. The sustainability reporting of publicly listed industrial companies in the Philippines is still developing and is fairly new as reporting sustainability reports has only been mandatory for publicly listed companies in 2019.